Catalytic Effects of High‐Valent Transition Metal Oxides on Different Carbonization Behaviours of Polyvinyl Alcohol. Issue 29 (12th October 2017) - Hu, Qiao; Liao, Jia‐Ying; Yu, Ran; Tang, Zhong‐Feng; Chen, Chun‐Hua
Abstract: Four different high‐valent transition metal oxides (VO2, Nb2 O5, Ta2 O5 and WO3 ) are investigated for the catalytic effect on the carbonization of polyvinyl alcohol. X‐ray diffraction, infrared carbon‐sulfur analyzer, transmission electron microscopy and Raman spectroscopy are employed to study the compositions and structures of the residual carbon and resulted metal oxides. The roles of different high‐valent transition metal oxides and specific surface areas are discussed in the high temperature carbon thermal reduction process for the residue and form of carbon. It is found that VO2 as the most effective catalyst and polyvinyl alcohol as the carbon source leads to the highest amount of carbon residue (21.34 wt%) and the lowest ratio of sp 3 to sp 2 (0.18). Abstract : With polyvinyl alcohol (PVA) as the carbon source, the catalytic effects of four high‐valent transition metal oxides (VO2, Nb2 O5, Ta2 O5 and WO3 ) for the PVA carbonization process are compared with each other. VO2 as a catalyst leads to the highest amount of carbon residue (21.34 wt%) while the form of carbon is mainly sp 2 hybridization. VO2 and WO3 also act simultaneously as oxidizers to promote the dehydrogenation step.